2019
DOI: 10.21608/epsj.2019.63534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatments During Hatching Eggs Storage on Hatchability Traits and Chick Quality

Abstract: The purpose of this study was to investigate the efficacy of short periods of incubation during egg storage (SPIDES) on hatchability, embryonic mortality, incubation time and chick quality of broiler breeder hatching eggs stored for 15 days. A total of 15510 hatching eggs were collected from 49-wk-old Arbor Acres broiler breeders flock. Eggs were divided into four groups. First group was stored for 5 days without heat treatment (Fresh eggs). Second group was stored for 15 days and heated one time at the fifth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Furthermore, hatchability was enhanced with a heat treatment that included four 4-h pre-incubations spaced 4–5 days apart over a period of 3 weeks of storage at 16 °C mainly by reducing late embryo mortality rather than early death (Dymond et al, 2013 ). Numerous additional authors, on the other hand, have shown that warming therapy before incubation lowers early mortality (0–7 days) (Fasenko et al, 2001b ; Gucbilmez et al, 2013 ; Nicholson et al, 2013 ; Reijrink et al, 2010 , 2009 ) and late embryo mortality especially in comparison to unheated eggs (Abdel-Halim et al, 2015 ; Ebeid et al, 2017 ; Gharib, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, hatchability was enhanced with a heat treatment that included four 4-h pre-incubations spaced 4–5 days apart over a period of 3 weeks of storage at 16 °C mainly by reducing late embryo mortality rather than early death (Dymond et al, 2013 ). Numerous additional authors, on the other hand, have shown that warming therapy before incubation lowers early mortality (0–7 days) (Fasenko et al, 2001b ; Gucbilmez et al, 2013 ; Nicholson et al, 2013 ; Reijrink et al, 2010 , 2009 ) and late embryo mortality especially in comparison to unheated eggs (Abdel-Halim et al, 2015 ; Ebeid et al, 2017 ; Gharib, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…When investigating the circumstances under which mass egg incubation is occurring in hatcheries, currently, it is obvious that getting the best hatching synchronization and shortening the gap between the first and last chicks to hatch outweighs the length of incubation period. Except for species-specific differences, it has been demonstrated that the mother’s age, the genetic makeup, and the weight of the eggs, as well as the amount of time and the environment in which they were kept before incubation, can all affect how long it takes to hatch an egg (Abdel-Halim et al, 2015 ; Fasenko, 2007 ; Ruiz and Lunam, 2002 ; Vieira et al, 2005 ). Now that each of these elements is considered in industrial hatcheries, with the intention of treating all eggs during storage similarly and hatching them at the same time using the same reproductive flocks (van de Ven, 2012 ), however, Tong et al ( 2013 ) detected that hatch window ranges from 24 to 48 h. Consequently, in contrast to precocial birds’ natural development, which takes 3 to 24 h and has at least 3rd eggs in its clutch (Eichholz and Towery, 2010 ), the reason for this discrepancy is that the insignificant small number of eggs in a normal clutch is in comparison with hundreds of thousands of eggs placed in a hatching device.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation